Legal Protection and Certainty of Land Ownership in Post-Disaster Recovery: Evidence from Indonesia, Spain, and Oman - Maisa, Maisa; Nafri , Muh; Amri, Amriana; Alejandro, Sergi Fernandez; Ezzerouali, Souad Ahmed (Journal of Law and Legal Reform, 2026)
This study investigates the legal protection and certainty of land ownership in post-disaster recovery, with a comparative focus on Indonesia, Spain, and Oman. It particularly examines the aftermath of the 2018 earthquake, tsunami, and liquefaction in Central Sulawesi, Indonesia, and contrasts it with recovery efforts in Spain and Oman. Using a descriptive empirical legal approach, the study explores the legal protections for disaster victims, the restoration of land ownership, and challenges in rebuilding. In Indonesia, the 2018 disaster in Petobo Village is analyzed through Governor Regulation No. 10 of 2019, which governs post-disaster rehabilitation and reconstruction. The law stipulates the rights to land restitution and housing reconstruction; however, delays in permanent housing construction have hindered the realization of victims’ rights. In Spain, the recovery from the 2011 earthquake in Lorca is examined under the Royal Decree 307/2005, which regulates compensation for victims of natural disasters. Despite the law’s aim to safeguard land rights and accelerate recovery, significant delays occurred in land restitution and compensation for affected property owners. In Oman, the Land Expropriation Law (Royal Decree No. 6/2008) and Cyclone Gonu Recovery Law provide mechanisms for land distribution and compensation, but challenges arose due to incomplete property registration and inconsistent enforcement, which delayed recovery efforts. By comparing these legal frameworks, the study highlights the differences in land governance and proposes recommendations for strengthening legal protections and ensuring faster, more efficient recovery in post-disaster contexts.